1998
DOI: 10.2307/3547060
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Species Richness: The Michaelis-Menten Model Revisited

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org..Wiley-Blackwell and Nordic Society Oikos are collaborating with JSTOR to digitize, preserve and extend access to Oikos.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 22 publications
2
72
0
2
Order By: Relevance
“…Rarefaction curves were calculated using EstimateS (http://viceroy.eeb.uconn.edu/estimates) using individual-based curves (sampling without replacement) (24) based on the Michaelis-Menten models (49). We note that the impact on the shape of species-accumulation curves of different community structures is an area of active research (50); with the data at hand (six samples), we are unable to satisfactorily explore this issue.…”
Section: Methodsmentioning
confidence: 99%
“…Rarefaction curves were calculated using EstimateS (http://viceroy.eeb.uconn.edu/estimates) using individual-based curves (sampling without replacement) (24) based on the Michaelis-Menten models (49). We note that the impact on the shape of species-accumulation curves of different community structures is an area of active research (50); with the data at hand (six samples), we are unable to satisfactorily explore this issue.…”
Section: Methodsmentioning
confidence: 99%
“…However, caution should be exercised in equating the extrapolated S max with true total species richness. While certain studies have emphasized the Michaelis-Menten model's empirical accuracy and robustness (de Caprariis et al 1976(de Caprariis et al , 1981, others have demonstrated its bias in heterogeneous environments (Keating 1998). Yet, if species accumulation curves can be demonstrated to adequately represent uniform sampling of relatively homogenous environments, extrapolation to true species richness should still be possible (Colwell and Coddington 1994).…”
Section: Discussionmentioning
confidence: 99%
“…An asymptotic equation is then fit to this curve, and the estimate of the asymptote parameter is the estimate of species richness. The function most often used, and the one used in this report, is the Michaelis-Menten equation (Clench 1979, Soberon and Llorente 1993, Colwell and Coddington 1994, Chazdon et al 1998, Keating and Quinn 1998. Parameter values were estimated using Raaijmakers' (1987) maximum likelihood estimators for the Eadie-Hofstee transformation, as outlined in Colwell and Coddington (1994).…”
Section: Richness Estimation and Evaluation Of Estimatorsmentioning
confidence: 99%